2000
DOI: 10.1046/j.1365-2702.2000.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

School nurses’ operational modes and ways of collaborating in caring for child abusing families in Finland

Abstract: • The purpose of the study was to explicate and conceptualize school nurses’ work and working methods while caring for child abusing families. Child abuse in the family refers to physical or psychological abuse, sexual abuse or neglect by parents or other caregivers. • Data were collected using semi‐structured interviews with broad themes from Finnish school nurses (n=20). School nurses were selected so that the sample represented a varied experience of school health services in various schools, differing in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Buckley's research suggested that this could be an effective approach (Buckley 2005). The findings in Paavilainen et al. 's (2000) study offer an interesting perspective on a more active role for school nurses.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Buckley's research suggested that this could be an effective approach (Buckley 2005). The findings in Paavilainen et al. 's (2000) study offer an interesting perspective on a more active role for school nurses.…”
Section: Discussionmentioning
confidence: 76%
“…A study of calls to Childline (Scotland) showed that few children would call to seek help about neglect, whereas they would call about physical abuse and sexual abuse (Vincent & Daniel 2004). Hints about child help‐seeking behaviour emerge from a Finnish study on the role of school nurses who noted a ‘first sign pointing to problems was often the fact that the child consulted the school nurse more frequently than before’ (Paavilainen et al. 2000, p. 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They might be able to suggest useful ways to develop services or indicate what kind of clients or families do not benefit from the support provided. In family work, for instance, withdrawal has turned out to be related to the caregiver's work orientation, the communication between families and the caregivers as well as the dysfunction of families (Paavilainen et al 2000, McKay et al 2001, Onyskiw 2002, Harrison et al 2004.…”
Section: Resultsmentioning
confidence: 99%
“…The nurse's personal working style and orientation, individual characteristics and ability to establish a confidential relationship affect the client's experiences. (Lynn-McHale & Deatrick 2000, Paavilainen et al 2000, Harrison et al 2004, Hä ggman-Laitila 2005.…”
Section: Limitationsmentioning
confidence: 99%